1997
DOI: 10.1038/sj.bmt.1700718
|View full text |Cite
|
Sign up to set email alerts
|

Decreased interleukin 10 and increased interferon-γ production in patients with chronic graft-versus-host disease after allogeneic bone marrow transplantation

Abstract: Summary:In humans, there are few reports dealing with cytokine production in chronic GVHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 2 publications
1
33
1
Order By: Relevance
“…19,22 On the other hand, other studies favor a Th1-driven mechanism of cGVHD in both murine and human systems. [23][24][25] However, the current study could not detect any significant difference in IL-4 or IFN-g production from CD4 þ T cells between patients with and without cGVHD. Although the reason for the discrepancy in the results between the previous reports and this study is currently unknown, it might be related to the difference in the severity of cGVHD examined.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…19,22 On the other hand, other studies favor a Th1-driven mechanism of cGVHD in both murine and human systems. [23][24][25] However, the current study could not detect any significant difference in IL-4 or IFN-g production from CD4 þ T cells between patients with and without cGVHD. Although the reason for the discrepancy in the results between the previous reports and this study is currently unknown, it might be related to the difference in the severity of cGVHD examined.…”
Section: Discussioncontrasting
confidence: 44%
“…20 In addition, several reports have demonstrated that type 2 cytokines are associated with cGVHD, 21,22 whereas other studies favor the significance of Th1 balance in cGVHD. [23][24][25][26] In this study, we analyzed the cytokine production of T cells in the chronic phase of patients who underwent allo-HSCT and found that IL-4-producing CD8 þ T cells are closely associated with cGVHD.…”
Section: Gvhd; Hsct; Cytokinesmentioning
confidence: 99%
“…30 It was observed in a murine cGVHD model that production of Th2 cytokines was enhanced and Th1 cytokines impaired, suggesting that activation of Th2 cells is responsible for autoantibody formation and immunosuppression in cGVHD. 31 However, Körholz et al 32 reported a significant decrease in IL-10 production by mononuclear cells activated in vitro in cGVHD patients. It is not clear whether this discrepancy is due to a different pathogenesis of human cGVHD and murine cGVHD, or to a difference in the method of testing serum samples or samples from cells activated in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…51 Chronic GVHD has been proposed by Ferrara and colleagues 52 to be a Th2-mediated disease, but recent studies demonstrating upregulation of Th1 cytokines IFN␥ and IL-12 in peripheral blood mononuclear cells implicate, in part, a Th1-driven mechanism similar to that seen in acute alloreactivity. 49,52,53 To elucidate the immunomodulatory effects of ECP on putative effectors of cGVHD, we initiated a clinical trial to evaluate lymphocyte and dendritic cell function in patients receiving ECP for 2 consecutive days every 2 weeks. 54 The median time from BMT in our population was 667 days (range, 101-600 days).…”
Section: Immunomodulatory Mechanisms Of Ecp In Gvhdmentioning
confidence: 99%